Perennialism and the Religious Common Platform of Mystical Tradition in Java - Zulfan Taufik; Syafwan Rozi (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2021)
This article examines perennials’ understanding through the Javanese mysticism tradition that has developed before and after the arrival of Islam. The focus on perennials in this article is based on recognizing and equality of noble values in every religion that has ever developed in Javanese society, such as Buddhism, Hinduism, and Islam. Previous studies have emphasized that Javanese mysticism is studied from the acculturation of culture with religion. Even this understanding of religion is considered the antithesis of religious exclusivism and conservatism that is currently developing. It is just that the study of Javanese mysticism in the approach of religious perennials is infrequent and limited. This study uses a library research method to reveal the values of mysticism that develop across the religious boundaries of Javanese society. The findings of this study are that there are several teachings of Javanese mysticism, including the conceptions of tantrism, tantularism, and manunggaling kawula gusti. These conceptions illustrate the openness of Javanese society to various religions. They believe that in religions, there is a commonality in ultimate truth or divinity and mystical unity.